Teaching About Better Family–Clinician Partnerships in High-Risk Pediatric Asthma Care - Michalopoulou, Georgia (J Patient Exp, 2016)
Family–clinician partnership including communication, trust, respect, and power leveling is essential in pediatrics. Our case study illustrates elements supporting/hindering partnership in a high-risk urban pediatric asthma clinic. Data from observation of a 100-minute visit were qualitatively analyzed by applying codes to themes, using family-centered principles. Three key categories emerged from examining interactions and their sequencing: (1) partnership supported, (2) partnership missed, and (3) partnership hindered. Practitioners must become more sensitive to families’ lives and skilled in family-centered care delivery. Clinician education about partnership can help with negotiating workable treatment strategies for complex conditions such as asthma and reduce health disparities.